2009
DOI: 10.1113/jphysiol.2008.165217
|View full text |Cite
|
Sign up to set email alerts
|

De novo expression of Kv6.3 contributes to changes in vascular smooth muscle cell excitability in a hypertensive mice strain

Abstract: Essential hypertension involves a gradual and sustained increase in total peripheral resistance, reflecting an increased vascular tone. This change associates with a depolarization of vascular myocytes, and relies on a change in the expression profile of voltage-dependent ion channels (mainly Ca 2+ and K + channels) that promotes arterial contraction. However, changes in expression and/or modulation of voltage-dependent K + channels (Kv channels) are poorly defined, due to their large molecular diversity and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
89
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(99 citation statements)
references
References 46 publications
9
89
0
1
Order By: Relevance
“…Consistent with our findings, the K V 2.1 subunit has been reported to be the major K V subunit in rat and mouse DSM (9,17,41,56). From the electrically silent subunits that we identified (K V 6.2-6.3, K V 8.2, and K V 9.1-9.3), only K V 6.3 and K V 9.3 have been reported to contribute to the ScTx1-sensitive current by forming K V 2.1/6.3 and K V 2.1/9.3 ScTx1-sensitive K V heterotetramers (14,15,40). It is also well known that the K V 9.3 subunit combines only with the K V 2.1 subunit to form a functional heterotetramer and remains electrically silent if expressed alone in artificial systems (14, 32-34, 44, 45).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Consistent with our findings, the K V 2.1 subunit has been reported to be the major K V subunit in rat and mouse DSM (9,17,41,56). From the electrically silent subunits that we identified (K V 6.2-6.3, K V 8.2, and K V 9.1-9.3), only K V 6.3 and K V 9.3 have been reported to contribute to the ScTx1-sensitive current by forming K V 2.1/6.3 and K V 2.1/9.3 ScTx1-sensitive K V heterotetramers (14,15,40). It is also well known that the K V 9.3 subunit combines only with the K V 2.1 subunit to form a functional heterotetramer and remains electrically silent if expressed alone in artificial systems (14, 32-34, 44, 45).…”
Section: Discussionmentioning
confidence: 96%
“…Stromatoxin-1 (ScTx1), a spider venom peptide isolated from the African tarantula (Stromatopelma calceata), was recently identified as a highly selective inhibitor of the K V 2.1, K V 2.2, and K V 4.2 homotetramers as well as the K V 2.1/6.3 and K V 2.1/9.3 heterotetramers (14,15,40). Studies in neurons, cerebral arteries, urethra, and DSM have confirmed that ScTx1 is a useful pharmacological tool to study the functional role of these K V channels (1,6,9,37,40,61).…”
mentioning
confidence: 99%
“…6 However, looking at the expression levels of the Kv1 subfamily members ( Figure 1A), it is noticeable that contractile VSMC have a predominant expression of Kv1.5 channels (whose functional contribution has been characterized [16][17][18] ); whereas Kv1.5 expression is almost absent in cultured VSMC, where Kv1.3 expression predominates. Data from 3 different vascular beds ( Figure 1B) show that the Kv1.5 to Kv1.3 switch on proliferation is conserved in VSMC from conduit and resistance arteries, suggesting that the ratio Kv1.3:Kv1.5 is a representative parameter of the VSMC phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…The specificity and potency of diphenyl phosphine oxide-1 blocking Kv1.5 currents was determined in parallel experiments using heterologously expressed Kv1.5 channels (data not shown), and the fraction of Kv1 current in both mesenteric and femoral VSMC was previously defined by using the correolide-sensitive fraction of the outward K + current. 6,18 The fact that a proproliferative role of Kv1.3 channels was described in VSMC from several human vessels 6,7 could reflect an obligatory association of Kv1.3 channels with vascular remodeling, increasing its value as a new therapeutical target. Although there are several other ion channels (including TRPC1, 2 T-type calcium channels, 1 Kv3.4 channels, 3,4 and IK1 channels 5,25 ) whose expression and/or function has been linked to VSMC proliferation, the information regarding conservation across different vascular beds and/or species is missed for most of these candidates.…”
Section: Discussionmentioning
confidence: 99%
“…Ionic currents were recorded at room temperature (20-25°C) using the whole-cell configuration of the patch-clamp technique as previously described [27,30]. Membrane potential (V M ) measurements were obtained at RT using the perforated patch technique [39].…”
Section: Electrophysiological Methods and Intracellular Calcium Measumentioning
confidence: 99%